Effect of Personality Traits and Wisdom on Perceived Stress among Research Scholars - Kainat Naseer; Dr. Sajid Mahmood Alvi; Ambreen Akhtar (International Journal of Business and Economic Affairs, 2024)
The study was conducted to determine the effects of personality traits and wisdom on perceived stress among research scholars. The current research also investigated gender differences. The present study used the perceived stress scale, Goldberg’s Big Five inventory, and wisdom three-dimensional scales for data collection—a sample of the present study comprised of students, (n=200). For data analysis, Pearson correlation and independent sample t-test were used. The result revealed that males score high on wisdom as compared to females. There is a negative correlation between wisdom and perceived stress. The findings have theoretical applied significance in the role of personality traits and wisdom on perceived stress among research scholars.